PENGARUH BIAYA OPERASIONAL TERHADAP PROFITABILITAS PT INDOFOOD SUKSES MAKMUR Tbk PERIODE 2020-2023 - Febrianto, Ahmad; HIilda Zamrotul Firdausiah (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
PT. Indofood Sukses Makmur is a well-known processing company in Indonesia. The purpose of this study is to determine the effect of operating costs on profitability at PT. Indofood Sukses Makmur Tbk for the period 2020-2023. Where the tendency of operating costs has increased while profitability at PT Indofood has increased growth every year. The method used in this study is a descriptive method using a quantitative approach. The data used is secondary data in the form of the company's financial reports for 2020-2023. Operating costs have experienced rapid growth every year. To determine the effect of operating costs on profitability, statistical testing is used. Statistical testing is used in normality tests, the use of regression, correlation coefficients, determination coefficients, t-tests also using the SPSS 16 application. From the results of simple linear regression calculations and correlation coefficients, operating costs and profitability have a Pearson correlation value of 0.641, which is a strong correlation level. so that the level of influence of operating costs on profitability at PT Indofood is 0.213 and the rest, namely 0.787, is influenced by other factors that were not studied. The results of the t-test value obtained t0 0,520 ≥ ta 2,920, so this value means that operational costs do not affect profitability.